Knowledge, Attitude and Practice of Modern Contraceptives (especially Spacing Methods) in Acceptors and Non-acceptors of Tubectomy - Devidas T Khedkar; Jyoti Landge; Girish Thite; Amitav Banarjee (Medsci Publications, 2018)
Context: From National Health Policy 1983 to NHP 2017, three demographic goals are constantly persuaded:  to reduce CBR (Crude Birth Rate) to 21, NRR (Net Reproduction Rate) to 1 and raise the CPR (Couple Protection Rate) to at least 60%, which are not yet reached and could be achieved by promoting spacing contraceptive methods. NFHS-4 reveals that, the contribution of all five spacing methods to all modern contraceptives was only 11.5%.  Objectives:  This study was intended to assess and compare the knowledge, attitude and practice of modern contraceptives, especially spacing methods, amongst acceptors and non acceptors of tubectomy. Methodology: An observational, analytical, case-control study design was used. The data on acceptors and non-acceptors of tubectomy, 137 each, were collected by trained staff and analyzed by using 'epi-info', and 'WIN-PEPI' soft ware. Results: The proportions of acceptors and non-acceptors with adequate knowledge of contraception were 77% and 81% respectively and that with favorable attitude, were 96% and 87% respectively, but only 45% acceptors and 43% non acceptors used some temporary contraception. Conclusions:  Number and sex of children is the significant determinant for use of contraception. Proportions of acceptors and non acceptors of tubectomy with unfavorable attitude towards contraceptives were 4% and 13% respectively and this difference was statistically highly significant.